Minimal Clinically Important Difference and Patient Acceptable Symptom State in Patients With Knee Osteoarthritis Treated With PRP Injection. Issue 10 (4th October 2021) - Boffa, Angelo; Andriolo, Luca; Franceschini, Marco; Di Martino, Alessandro; Asunis, Emanuela; Grassi, Alberto; Zaffagnini, Stefano; Filardo, Giuseppe
Background: Although several injection-based treatments have been proposed to address knee osteoarthritis (OA), it is often difficult to understand the clinical relevance of the obtained results. The psychometric measures of minimal clinically important difference (MCID) and Patient Acceptable Symptom State (PASS) were developed to better interpret study findings. Purpose: To establish the MCID and the PASS for the International Knee Documentation Committee (IKDC) Subjective score and the Knee injury and Osteoarthritis Outcome Score (KOOS) in patients treated with intra-articular platelet-rich plasma (PRP) injections for knee OA. Study Design: Case series; Level of evidence, 4. Methods: This study included 215 patients with knee OA (68% men, 32% women; age, 53.2 ± 11.3 years; body mass index, 26.8 ± 4.3 kg/m 2 ) who underwent intra-articular PRP injections. Patients were assessed through the IKDC Subjective score and KOOS subscales, and the MCID and the PASS for both measures were independently calculated at 6 and 12 months post-injection. The MCID was calculated using the value equal to half of the standard deviation of the overall cohort improvement. The PASS was assessed using a 2-point scale ( satisfied or not satisfied ), with threshold values being detected through a receiver operating characteristic curve analysis and the Youden index to maximize the sensitivity and the specificity of the threshold values. Results: All scores improved significantly from baseline to 6 months and baseline to 12 months ( P < .001 for all scores). All scores were stable from 6 to 12 months except for the KOOS Quality of Life subscale, which improved further ( P = .033). For the IKDC, the MCID values were 8.6 and 8.5 points and the PASS scores were 59.7 and 62.1 at 6 and 12 months, respectively. Overall, the MCID and the PASS for all KOOS subscales remained constant at the 2 follow-up points. The percentage of patients who achieved the MCID and the PASS was higher than 85% at both 6 and 12 months post-injection. Conclusion: This study provided the MCID and PASS thresholds for the IKDC and KOOS scores in patients with knee OA treated with PRP injections. These psychometric measures may allow a better interpretation of the clinical relevance of injection-based treatment outcomes for knee OA.